How Demographics, Adversity Quotient, and School Engagement Impact Academic Resilience in Bilingual and Islamic Boarding Schools - Mayangsari, Marina Dwi; Rachmah, Dwi Nur; Febriani, Wury Utami; Rahman, Nur Khofifah; Luthfi, Muhamad; Hanifa, Indah Mutia (International Journal of Islamic Educational Psychology, 2025)
Academic resilience is paramount for students to persevere even in challenging, risky, and unfavorable circumstances. This study investigated the influence of demographic factors, such as age and gender, as well as psychological factors, specifically adversity quotient and school engagement, on students' academic resilience. The participants in this study consisted of 262 high school students from two Boarding Schools in South Kalimantan. Participants were asked to complete the scales for the variables and respond according to their current circumstances. This quantitative study collected data via Zoom Meetings and analyzed it using hierarchical regression. Findings from the analysis indicated that demographic factors did not play a significant role in academic resilience R2 = 0.032, F(2.259) = 4.305, p = 0.014, while psychological factors showed significant results (R2 = 0.390, F(2.257) = 75.267, p = 0.000. Although demographic factors such as age and gender had no significant effect on academic resilience, psychological factors such as adversity quotient (β = 0.547, t = 9.694, p < 0.05) and school engagement (β = 0.116, t = 2.035, p < 0.05) had a strong influence. These findings emphasized the importance of the adversity quotient in shaping how students view academic challenges as opportunities for growth and school engagement as a key driver in enhancing academic resilience. The main contribution of this research lies in educational psychology, particularly in efforts to improve educational quality by providing moral and psychological support services that strengthen students’ resilience and academic performance.